10 pī Sān Ratthathammanūn Thai : sū thotsawat mai khō̜ng nitirat Thai (Samnakngān Sān Ratthathammanūn, 2008)
On the roles, duties and performance of and contributed articles on San Ratthathammanun, the Constitutional Court of Thailand; volume brought out at its 10th anniversary.